2004
DOI: 10.1103/physrevlett.92.033201
|View full text |Cite
|
Sign up to set email alerts
|

Control of Atomic Collisions by Laser Polarization

Abstract: Atomic collision pairs in a light field form a microscopic interferometer. The light acts as the beam splitter and controls at the same time the amplitudes and phases of the interfering waves. We demonstrate the complete tunability using linear and elliptic polarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The main experimental challenge, the superposition of a laser beam, an energetic ion or electron beam, and a target has been mastered very recently [6]. The possible control of slow atom-atom collisions by laser light has been demonstrated with a somewhat different setup [7]. On the theoretical side refined methods for the description of laserassisted collisions have been worked out, implemented and tested on prototype scattering systems.…”
Section: Introductionmentioning
confidence: 99%
“…The main experimental challenge, the superposition of a laser beam, an energetic ion or electron beam, and a target has been mastered very recently [6]. The possible control of slow atom-atom collisions by laser light has been demonstrated with a somewhat different setup [7]. On the theoretical side refined methods for the description of laserassisted collisions have been worked out, implemented and tested on prototype scattering systems.…”
Section: Introductionmentioning
confidence: 99%
“…LiVSe2 was found to be a paramagnetic metal down to 2 K. Transition metal compounds with a geometrically frustrated lattice, such as a triangular and a pyrochlore lattice, often form a valence bond solid (VBS) state at low temperatures. When the t 2g orbitals are partially occupied, utilizing orbital degrees of freedom, complex "molecular" clusters in a spin singlet state are often formed: trimer in LiVO 2 [1,2,3,4,5], heptamer in AlV 2 O 4 [6], helical dimer in MgTi 2 O 4 [7] and octamer in CuIr 2 S 4 [8]. A VBS state was found also in organic systems with geometrical frustration [9].…”
mentioning
confidence: 99%
“…Metal-insulator transitions with the formation of unusual structures are observed in many spinels. The recent examples are MgTi 2 O 4 [2], CuIr 2 S 4 [3] or AlV 2 O 4 [4]. Structural studies have shown that in all these cases rather unusual structural modifications take place, which often can be described as the formation of molecular clusters.…”
Section: Formation Of Dimers In Spinelsmentioning
confidence: 99%
“…Structural studies have shown that in all these cases rather unusual structural modifications take place, which often can be described as the formation of molecular clusters. In MgTi 2 O 4 there appears a "chiral" structure [2], in CuIr 2 S 4 Ir octamers are formed [3], but both these phenomena can in fact be explained by the formation of Ti or Ir singlet dimers, which in a frustrated lattice of B-sites of a spinel finally give rise to these chiral or octamer structures [5]. And in AlV 2 O 4 the molecular clusters formed consist of 7 vanadiums -real large "heptamer molecules".…”
Section: Formation Of Dimers In Spinelsmentioning
confidence: 99%